Antibiotic Susceptibility Pattern of Gram-negative Isolates of Lower Respiratory Tract Infection - Nepal, Rakshya; Shrestha, Basudha; Joshi, Deepak Man; Joshi, Rajesh Dhoj; Shrestha, Sanjit; Singh, Anjana (Journal of Nepal Health Research Council, 2018)
Background: Lower respiratory tract infection is a common cause of morbidity and mortality worldwide. A crosssectional study was carried out with an objective to study the antibiogram of Gram-negative isolates of patients with lower respiratory tract infection visiting Kathmandu Model Hospital. Methods: A total of 274 specimens including sputum, endotracheal aspirates, suction tips were cultured as per standard microbiological technique. Antibiotic susceptibility and detection of Extended-spectrum beta- lactamases (ESBLs) were performed following Clinical Laboratory Standard Institute (CLSI 2014) guidelines. Results: Respiratory pathogens were recovered from 24.6% (n=65) cases. Klebsiella pneumoniae (40%) was the commonest isolates. The highest prevalence of multidrug-resistance (69.23%) was observed in Acinetobacter calcoaceticus baumannii complex. Extended-spectrum beta- lactamases were detected in Escherichia coli (n=4), Klebsiella pneumoniae (n=4) and Acinetobacter calcoaceticus baumannii complex (n=1). Conclusions: High prevalence of multidrug-resistance and extended- spectrum beta- lactamase producers were observed in respiratory isolates. For effective management of lower respiratory tract infections, an ultimate and detailed microbiological diagnosis and susceptibility testing is required.